Feather mercury concentrations in omnivorous and granivorous terrestrial songbirds in Southeast Michigan - Bajracharya, Saria Sato; Zahor, Dorothy L.; Glynn, Kenneth J.; Gratz, Lynne E.; Cornelius, Jamie M. (Ecotoxicology (London), 2022)
Sublethal exposure to methylmercury (MeHg) can have consequences for the reproductive, neurological, and physiological health of birds. Songbirds, regardless of trophic position, are often exposed to mercury (Hg) and may be at risk for health effects – especially if they inhabit a place that is subject to high Hg atmospheric deposition and/or have local conditions that are prone to methylation. This study investigates Hg concentrations in terrestrial songbirds of Southeast Michigan, where historical and present-day anthropogenic emissions of heavy metals are elevated. We collected tail feather samples from 223 songbirds across four different species during summer and fall of 2018 and 2019. The mean (±SE) Hg concentration across all samples was 103 ± 3.43 ng/g of dry feather weight. Mercury concentration varied significantly among species, and by age and site in some species, but not by sex. Mean concentrations were nearly seven times higher in two omnivore species, American robin (Turdus migratorius ) and European starling (Sturnus vulgaris ), than in the two granivore species, American goldfinch (Spinus tristus ) and house sparrow ( Passer domesticus ). Juveniles had higher feather Hg concentrations than adults in all species except American goldfinches - which feed their young primarily seeds, further supporting a role of diet in exposure. We also found a negative correlation between Hg concentration and body condition in American robins, but further research is needed to verify this relationship. While our sample concentrations do not exceed the threshold for sublethal effects, our findings provide insight into the patterns of Hg concentrations in terrestrial songbirds, which may help in understanding Hg exposure pathways, bioaccumulation and risks in terrestrial species.